The Capital Inflows Problem : Concepts and Issues - Reinhart, Carmen (IMF Policy Discussion Papers; Policy Discussion Paper, 1993)
Since 1990 capital has started to move from industrial countries to developing regions like Latin America, the Middle East and parts of Asia. Reentry into international capital markets is a welcome turn of events for most countries. However, capital inflows are often associated with inflationary pressures, a real exchange rate appreciation, a deterioration in the current account, and a boom in bank lending. This paper briefly examines how these inflows have altered the macroeconomic environment in a number of Asian and Latin American countries. The pros and cons of a menu of policy options are discussed.